"A Force for Good": Army-Building After War in Liberia. Issue 3 (2nd July 2020) - Joyce, Renanah Miles
ABSTRACT: International efforts to reconstruct weak states after war have increased in recent years. These endeavors often focus on rebuilding militaries given the importance of strong and professional militaries in preventing conflict relapse. What explains variation in military-building outcomes in post-conflict states? The literature on statebuilding and security sector reform suggests a number of factors that are thought to ameliorate statebuilding dilemmas. This article identifies three central mechanisms from the literature and evaluates them using evidence from a case study of post-conflict army-building in Liberia. The findings show that the voluntary nature of cooperation matters strongly for the successful outcome in Liberia, as does donor identity, albeit differently than as predicted by theory. The role of local ownership receives somewhat weak support, however, which is surprising in light of its importance in the literature. These results have significant implications for theories of statebuilding and security assistance policies.